RAGAM BAHASA DALAM PENGGUNAAN BAHASA PERSUASIF PADA APLIKASI SHOPEE: KAJIAN SOSIOLINGUISTIK - Inzana, Yuyun; Gusnawaty, Gusnawaty; Said, Ikhwan M. (Lingua, 2021)
This research was inspired by the phenomenon of using a variety of languages and has a variety of languages that have different characteristics from one region to another, from one country to another. The purpose of this study is to describe the language selection that is widely used by sellers in the use of invitation sentences to promote products being sold to make them more attractive in the Shopee online shopping application. The research method uses descriptive methods with qualitative analysis. The results showed that the language of invitation in the Shopee application that we often use is non-standard language and is not in accordance with KBBI. Code mixing and code switching occur in informal situations when delivering messages to emphasize information in interacting with one another. The form of mixed code and the form of code switching between Indonesian and English and slang is the form of words.